2022
DOI: 10.1093/jme/tjac016
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Biting Behavior ofMansonia(Diptera, Culicidae) in Rural Settlements Near Porto Velho, State of Rondônia, Brazil

Abstract: Mansonia (Diptera: Culicidae) are known to cause discomfort to the local populations of Amazon. Considering the fact that the effective control of these mosquitoes can only be obtained by understanding their ecology and behavior, entomological monitoring becomes essential. In view of this, mosquitoes of the genus Mansonia were collected by human landing catches (HLC) from 2015 to 2019, in four locations of Porto Velho, Rondônia, Brazil. The collections were performed inside and outside the homes, once in every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…were observed during both the rainy and dry seasons. A similar trend was previously observed by Uttah et al [ 22 ] in Nigeria, Salako et al [ 16 ] in Benin, and Galardo et al [ 23 ] in Brazil. The presence of these mosquitoes all year round increases the risks of lymphatic filariasis transmission.…”
Section: Discussionsupporting
confidence: 91%
“…were observed during both the rainy and dry seasons. A similar trend was previously observed by Uttah et al [ 22 ] in Nigeria, Salako et al [ 16 ] in Benin, and Galardo et al [ 23 ] in Brazil. The presence of these mosquitoes all year round increases the risks of lymphatic filariasis transmission.…”
Section: Discussionsupporting
confidence: 91%
“…flaveola (Coquillett, 1906) in rural regions of the city of Porto Velho, Rondonia, Brazil. All the mentioned species above were also reported in a recent work by Galardo et al (2022) in rural settlements near Porto Velho, Rondonia and finally, Scarpassa et al (2022) reported new records for Mansonia dyari Belkin, Heinemann &Page, 1970 andMansonia indubitans Dyar &Shannon, 1925 in Rondonia, Brazil. Adults of the genus Mansonia are medium-sized mosquitoes with light or dark spots on their wings; in the females, the maxillary palpi are short and do not extend beyond the proboscis, whereas in males, the maxillary palpi are long (Forattini, 2002). Adult Mansonia females are aggressive and opportunistic during blood feeding, attacking any bird or mammal.…”
Section: Introductionsupporting
confidence: 53%
“…In two rural areas in Porto Velho, Rondonia, using BG-Sentinel traps, Gama et al (2012) collected approximately 1,145 mosquitoes of the genus Mansonia, including the same species collected in the present study. Recently, Galardo et al (2022) reported 96,766 Mansonia mosquitoes collected in rural settlements near Porto Velho, Rondonia over 5 year and Ma. titillans as the most abundant species.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study was conducted in the same region we sampled and Ma. titillans was the most abundant species collected outdoors and indoors, accounting for up to 77% of all specimens collected [ 10 ]. Our findings are corroborated by [ 10 ] since the results of the analysis focused on verifying the host distribution for each Mansonia species within each locality separate, we found a high relative abundance of Ma.…”
Section: Discussionmentioning
confidence: 99%
“…Species of the genus Mansonia feed preferentially at night, peaking at dawn and dusk [ 10 ]. The females readily bite and blood-feed on humans and domestic and wild vertebrate hosts [ 11 , 12 ], usually those that are close to the habitats of the immatures [ 13 ].…”
Section: Introductionmentioning
confidence: 99%